PENGARUH KECERDASAN INTERPERSONAL TERHADAP PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD - Anggi Cahya Ferdina; Nurmitasari; M. Arya Al Arsy; Irfiani Irfiani; Putri Nilasari; Fadillthus Soleha (Jurnal Genta Mulia, 2026)
This study aims to determine the effect of interpersonal intelligence on students’ active participation in mathematics learning at the elementary school level. Interpersonal intelligence refers to an individual’s ability to understand, empathize, and interact effectively with others, which is believed to play a vital role in enhancing students’ engagement in the learning process. This research employed a quantitative approach with a correlational design. The population consisted of 33 fourth-grade students at UPT SD Negeri 2 Karangsari in the 2025/2026 academic year, selected using the total sampling technique. Data were collected through questionnaires and analyzed using simple linear regression. The results indicated a positive and significant effect of interpersonal intelligence on students’ active participation, with a correlation coefficient (r) of 0.782 and a determination coefficient (r²) of 0.611. This means that 61.1% of the variation in students’ active participation is influenced by interpersonal intelligence. Therefore, improving students’ interpersonal intelligence can encourage them to become more active, communicative, and collaborative in mathematics learning.